Concepts in enterprise resource planning - Monk, Ellen F.; Wagner, Bret J. (New York : Cengage Learning, 2013)
This 4E reflects the latest trends and updates in ERP (Enterprise Resource Planning) software as well as introduces the basic functional areas of business and their relationships. Readers can see how integrated information systems help organizations improve business process and provide managers with accurate, consistent, and current data for making informed strategic decisions.
Ch. 1 Business Functions and Business Processes -- ch. 2 The Development of Enterprise Resource Planning Systems -- ch. 3 Marketing Information Systems and the Sales Order Process -- ch. 4 Production and Supply Chain Management Information Systems -- ch. 5 Accounting in ERP Systems -- ch. 6 Human Resources Processes with ERP -- ch. 7 Process Modeling, Process Improvement, and ERP Implementation -- ch. 8 RFID, Business Intelligence (BI), Mobile Computing, and the Cloud.
Includes bibliographical references and index.
Keywords: Manufacturing resource planning; Production management; Management information systems; Management information systems; Manufacturing resource planning; Production management